Evaluating Embodied Pedagogical Game Approach in the Learning of Selected Prepositions of Time - Nephawe, Farisani Thomas (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Competence in the use of prepositions is versatile because they mark special relationships between persons, objects, and locations. However, using prepositions of time is challenging for many. The research investigated embodied pedagogical game approach in learning selected prepositions of time by Grade 7 English First Additional Language learners at Tshiluvhi Primary School in Limpopo Province, South Africa. The research employed a quantitative approach to analyse data mathematically and statistically. The embodied cognitive approach was utilised because it holds that identification of prepositions of time is a fundamentally based cognitive aspect involving high mental constructs like judgement and thinking. A questionnaire was utilised to obtain data from the participants. Probability random sampling was used to sample 35 participants because it gave them an equal chance of participation in the research. A pilot study was conducted on learners who were not part of the sample to test the instrument’s reliability. A Statistical Package of Social Sciences Version 22 was employed for data analysis. Using embodied pedagogical game approach, pre-test results showed participants' poor competence while the post-test revealed an outstanding achievement in learning prepositions of time. The research recommends continuous use of the embodied pedagogical game approach in learning prepositions of time.